Selection of the Appropriate Phase Change Material for Two Innovative Compact Energy Storage Systems in Residential Buildings - Gabriel Zsembinszki (Applied Sciences, 2020)
The implementation of thermal energy storage systems using phase change materials to support the integration of renewable energies is a key element that allows reducing the energy consumption in buildings by increasing self-consumption and system efficiency. The selection of the most suitable phase change material is an important part of the successful implementation of the thermal energy storage system. The aim of this paper is to present the methodology used to assess the suitability of potential phase change materials to be used in two innovative energy storage systems, one of them being mainly intended to provide cooling, while the other provides heating and domestic hot water to residential buildings. The selection methodology relies on a qualitative decision matrix, which uses some common features of phase change materials to assign an overall score to each material that should allow comparing the different options. Experimental characterization of the best candidates was also performed to help in making a final decision. The results indicate some of the most suitable candidates for both systems, with RT4 being the most promising commercial phase change material for the system designed to provide cooling, while for the system designed to provide heating and domestic hot water, the most promising candidate is RT64HC, another commercial product.